Fertilizantes foliares en el cultivo de alfalfa Cuf 101 (Medicago sativa L.) en la granja la colina c.a. del cantón arenills - El Oro - Ecuador - Macías Bustamante, Darwin Raúl (2013)
This research was conducted at the Farm Hill CA located at 1 kilometer of track Arenillas - Alamor of the Province of El Oro, the geographical location of 30O 34' 34.71ˮ south latitude and 80O 3̓ 49.46ˮ W and a height of 62 meters. The investigation lasted 4 months. A complete random design (DCA) with 5 replications and 10 m2 per experimental unit was applied. To establish differences between means Tukey test (P ≤ 0.05) was applied. The treatments were: T1 = Control, T2 = Evergreen, T3 = Saeta-Ca -K Best T4 = T5 = Bacter and plus. The variables under study were: plant height (AP) ratio leaves / stems (R / T) , the pre-flowering period (TP), biomass production (PB) and profitability (R). Best TP (32.20) recorded it and PB treatment T1 (16.99 kg ha-1) was recorded by treatment T2. The NT and RH / T are not influenced by the use of foliar fertilizers (P≤0.05). Best R the recorded T1 (87.14) and T3 (80.73), respectively Keyword: foliar fertilization, production, Cuf 101